Quantitative assessment of aflatoxin exposure and hepatocellular carcinoma (HCC) risk associated with consumption of select Nigerian staple foods - Wenndt, Anthony; Mutua, Florence; Grace, Delia; Thomas, Lian F.; Lambertini, Elisabetta (Frontiers in Sustainable Food Systems, 2023)
Aflatoxin contamination of staple grains and legumes has been linked to hepatocellular carcinoma (HCC) and other adverse health outcomes, constituting a substantial public health concern globally. Low-resource food environments in sub-Saharan Africa are often under-regulated and are particularly vulnerable to adverse health and nutrition outcomes associated with aflatoxin exposure. This study identifies levels of HCC risk in the northern Nigerian adult population, leveraging a systematic review of available evidence on aflatoxin contamination in Nigerian maize, groundnut, rice, cowpea, and soybean. Estimated dietary intake (EDI) was computed using publicly available dietary consumption data and a probabilistic quantitative risk assessment was conducted to determine the relative risk of HCC associated with consumption of selected aflatoxin-contaminated commodities. In total, 41 eligible studies reporting aflatoxin contamination were used to model the distribution of aflatoxin concentrations in Nigerian commodities. EDIs for maize, groundnut, rice, and cowpea exceeded the provisional maximum tolerable daily intake (PMTDI) level of 1 kgbw-1 day-1, with maize yielding the highest mean EDI (36.7 kgbw-1 day-1). The quantitative risk assessment estimated that 1.77, 0.44, 0.43, 0.15, and 0.01 HCC cases per year/100,000 population were attributable to aflatoxin exposure through maize, groundnut, rice, cowpea, and soybean, respectively. Sensitivity analysis revealed that aflatoxin concentration, dietary consumption levels, consumption frequency, and other variables have differing relative contributions to HCC risk across commodities. These findings constitute a novel multi-study risk assessment approach in the Nigerian context and substantiate existing evidence suggesting that there is reason for public health concern regarding aflatoxin exposure in the Nigerian population.